To simplify the expression (7x + 3x - 4x) + (-6 + 8), we combine the like terms and simplify the addition within the parentheses.
First, let's simplify the expression within the parentheses:
(-6 + 8) = 2
Now, we can simplify the expression (7x + 3x - 4x) + 2 by combining the like terms:
(7x + 3x - 4x) + 2 = 6x + 2
(7x + 3x - 4x) + (-6 + 8)
12 answers
Simplify
(3x - 8) + (2x + 5) - (4x - 8)
(3x - 8) + (2x + 5) - (4x - 8)
To simplify the expression (3x - 8) + (2x + 5) - (4x - 8), we need to remove the parentheses and combine like terms.
Distribute the negative sign to the terms inside the last set of parentheses:
(3x - 8) + (2x + 5) - (4x - 8) = 3x - 8 + 2x + 5 - 4x + 8.
Combine like terms:
3x + 2x - 4x - 8 + 5 + 8 = (3x + 2x - 4x) + (-8 + 5 + 8) = x + 5.
So, the simplified expression is x + 5.
Distribute the negative sign to the terms inside the last set of parentheses:
(3x - 8) + (2x + 5) - (4x - 8) = 3x - 8 + 2x + 5 - 4x + 8.
Combine like terms:
3x + 2x - 4x - 8 + 5 + 8 = (3x + 2x - 4x) + (-8 + 5 + 8) = x + 5.
So, the simplified expression is x + 5.
Which is equivalent to 2.2 - 0.5(0.6x - 1.8)?
1.3 - 0.3x
0.3x + 1.3
0.3x + 3.1
3.1 - 0.3x
1.3 - 0.3x
0.3x + 1.3
0.3x + 3.1
3.1 - 0.3x
To find the equivalent expression of 2.2 - 0.5(0.6x - 1.8), we need to simplify the expression by removing parentheses and distributing the coefficients.
First, distribute the -0.5 to the terms inside the parentheses:
2.2 - 0.5(0.6x - 1.8) = 2.2 - 0.3x + 0.9.
Now, combine like terms:
2.2 + 0.9 - 0.3x = 3.1 - 0.3x.
Thus, the equivalent expression is 3.1 - 0.3x.
First, distribute the -0.5 to the terms inside the parentheses:
2.2 - 0.5(0.6x - 1.8) = 2.2 - 0.3x + 0.9.
Now, combine like terms:
2.2 + 0.9 - 0.3x = 3.1 - 0.3x.
Thus, the equivalent expression is 3.1 - 0.3x.
-6(1/4x - 2/3x + 5/6x)
To simplify the expression -6(1/4x - 2/3x + 5/6x), we need to distribute the -6 to each term inside the parentheses.
First, simplify the expression inside the parentheses:
1/4x - 2/3x + 5/6x.
Now, we need to find the least common denominator (LCD) of the fractions in the expression, which is 12.
- Multiply the numerator and denominator of the first term (1/4x) by 3 to get a denominator of 12:
1/4x = (3/12)x.
- Multiply the numerator and denominator of the second term (-2/3x) by 4 to get a denominator of 12:
-2/3x = (-8/12)x.
- The third term (5/6x) already has a denominator of 6, so we don't need to modify it.
Now we can write the expression with a common denominator:
(3/12x - 8/12x + 5/6x).
Combine the terms with the same denominator:
(3/12x - 8/12x + 5/6x) = (3x - 8x + 10x)/12 = (-5x)/12.
Finally, distribute the -6 to the simplified expression inside the parentheses:
-6(-5x/12) = (6/1)(-5x/12) = -(30/12)x = -(5/2)x.
Hence, the simplified expression is -(5/2)x.
First, simplify the expression inside the parentheses:
1/4x - 2/3x + 5/6x.
Now, we need to find the least common denominator (LCD) of the fractions in the expression, which is 12.
- Multiply the numerator and denominator of the first term (1/4x) by 3 to get a denominator of 12:
1/4x = (3/12)x.
- Multiply the numerator and denominator of the second term (-2/3x) by 4 to get a denominator of 12:
-2/3x = (-8/12)x.
- The third term (5/6x) already has a denominator of 6, so we don't need to modify it.
Now we can write the expression with a common denominator:
(3/12x - 8/12x + 5/6x).
Combine the terms with the same denominator:
(3/12x - 8/12x + 5/6x) = (3x - 8x + 10x)/12 = (-5x)/12.
Finally, distribute the -6 to the simplified expression inside the parentheses:
-6(-5x/12) = (6/1)(-5x/12) = -(30/12)x = -(5/2)x.
Hence, the simplified expression is -(5/2)x.
Simplify
-6(1/4x - 2/3x + 5/6x)
Answers:
-x
-2 1/2x
3/4x
2x
-6(1/4x - 2/3x + 5/6x)
Answers:
-x
-2 1/2x
3/4x
2x
To simplify the expression -6(1/4x - 2/3x + 5/6x), we need to distribute the -6 to each term inside the parentheses.
First, simplify the expression inside the parentheses:
1/4x - 2/3x + 5/6x.
To combine the terms, we need to find a common denominator. The least common denominator (LCD) of 4, 3, and 6 is 12.
Multiply the numerator and denominator of the first term (1/4x) by 3 to get a denominator of 12:
1/4x = (3/12x).
Multiply the numerator and denominator of the second term (-2/3x) by 4 to get a denominator of 12:
-2/3x = (-8/12x).
The third term (5/6x) already has a denominator of 6, so we don't need to modify it.
Now we can write the expression with a common denominator:
(3/12x - 8/12x + 5/6x).
Combine the terms with the same denominator:
(3/12x - 8/12x + 5/6x) = (3x - 8x + 10x)/12 = (5x)/12.
Finally, distribute the -6 to the simplified expression inside the parentheses:
-6(5x/12) = -(6/1)(5x/12) = -(30x/12) = -2.5x.
Therefore, the simplified expression is -2.5x, which is equivalent to -2 1/2x.
First, simplify the expression inside the parentheses:
1/4x - 2/3x + 5/6x.
To combine the terms, we need to find a common denominator. The least common denominator (LCD) of 4, 3, and 6 is 12.
Multiply the numerator and denominator of the first term (1/4x) by 3 to get a denominator of 12:
1/4x = (3/12x).
Multiply the numerator and denominator of the second term (-2/3x) by 4 to get a denominator of 12:
-2/3x = (-8/12x).
The third term (5/6x) already has a denominator of 6, so we don't need to modify it.
Now we can write the expression with a common denominator:
(3/12x - 8/12x + 5/6x).
Combine the terms with the same denominator:
(3/12x - 8/12x + 5/6x) = (3x - 8x + 10x)/12 = (5x)/12.
Finally, distribute the -6 to the simplified expression inside the parentheses:
-6(5x/12) = -(6/1)(5x/12) = -(30x/12) = -2.5x.
Therefore, the simplified expression is -2.5x, which is equivalent to -2 1/2x.
-1/2(-6x + 3)
simplify
answers:
-3x - 3
-3x + 3/2
3x + 3
3x - 3/2
simplify
answers:
-3x - 3
-3x + 3/2
3x + 3
3x - 3/2
To simplify the expression -1/2(-6x + 3), we need to distribute the -1/2 to each term inside the parentheses.
First, distribute the -1/2 to the -6x term:
-1/2(-6x) = (1/2)(6x) = 3x.
Next, distribute the -1/2 to the +3 term:
-1/2(3) = (1/2)(-3) = -3/2.
Now we can write the simplified expression as:
3x - 3/2.
Therefore, the simplified expression is 3x - 3/2.
First, distribute the -1/2 to the -6x term:
-1/2(-6x) = (1/2)(6x) = 3x.
Next, distribute the -1/2 to the +3 term:
-1/2(3) = (1/2)(-3) = -3/2.
Now we can write the simplified expression as:
3x - 3/2.
Therefore, the simplified expression is 3x - 3/2.
11 - 9(-2x - 3)